Recent Progress on Graphene‐based Electrochemical Biosensors. Issue 1 (18th December 2015) - Zhang, Yu; Shen, Jingjing; Li, Huihua; Wang, Linlin; Cao, Dashun; Feng, Xiaomiao; Liu, Yuge; Ma, Yanwen; Wang, Lianhui
Abstract: The detailed records and conclusions on the important advancements in graphene‐based electrochemical biosensors have been reviewed. Due to their outstanding properties, graphene‐based materials have been widely studied for the accurate electrochemical detection of many biomolecules, which is extremely vital to the development of biomedical instruments, clinical diagnosis, and disease treatment. This review discusses the graphene research for the effective immobilization of enzymes, including glucose oxidase, horseradish peroxidase, and hemoglobin, etc., and the accurate detection of biomolecules, including glucose, hydrogen peroxide, dopamine, ascorbic acid, uric acid, nicotinamide adenine dinucleotide, DNA, RNA, and carcinoembryonic antigen, etc. In most of the cases, the graphene‐based biosensors exhibited remarkable performance with high sensitivities, wide linear detection ranges, low detection limits, and long‐term stabilities. Abstract : Recent progress on graphene‐based electrochemical biosensors, including enzymatic sensors, nonenzymatic sensors, DNA‐based sensors, and immunosensors, etc., are recorded and summarized. The accurate electrochemical detection of many biomolecules, such as glucose, hydrogen peroxide, dopamine, ascorbic acid, uric acid, nicotinamide adenine dinucleotide, DNA, RNA, and carcinoembryonic antigen, etc., has been achieved with excellent performance due to the outstanding properties of graphene‐based electrode materials.